Class, Race, and the US South : American Politics and Society through the Lens of Michael Goldfield's Work - Cyna, Esther; Maheo, Olivier; Melcher, Cody R. (Historical Materialism Book Series, 2026)
Class, Race, and the US South , a Festschrift for labour militant and political scientist Michael Goldfield, features original contributions from the most prominent contemporary historical-materialist social scientists and historians. The collection's uniting theme is that class, race, and the South are the most important mainsprings of American society. Combining labour history, southern history, and theoretical critiques of mainstream conceptualisations of racism, this work emphasises the working class as the primary driver of both reactionary and potentially revolutionary change.